2002
DOI: 10.1109/tvcg.2002.1021579
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional transfer functions for interactive volume rendering

Abstract: Most direct volume renderings produced today employ one-dimensional transfer functions which assign color and opacity to the volume based solely on the single scalar quantity which comprises the data set. Though they have not received widespread attention, multidimensional transfer functions are a very effective way to extract materials and their boundaries for both scalar and multivariate data. However, identifying good transfer functions is difficult enough in one dimension, let alone two or three dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
295
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(312 citation statements)
references
References 36 publications
0
295
0
8
Order By: Relevance
“…However, a multitude of parameters can affect the opacity at each sampling point: Transfer functions, segmentation data, clipping, other modalities, derived data. Additionally, transfer functions have to be differentiated further since multiple types exist (e.g., 1D intensity, 2D intensity-gradient, 2D LH [22], 3D [14]) and different segments may also have different transfer functions assigned to them. Incorporating all these parameters within the navigation algorithm would not be a trivial task, and if possible at all it would likely lead to code duplications, which would need to be updated to incorporate additional data sets or formats, new transfer function types, additional rendering parameters, etc.…”
Section: Design Considerationsmentioning
confidence: 99%
“…However, a multitude of parameters can affect the opacity at each sampling point: Transfer functions, segmentation data, clipping, other modalities, derived data. Additionally, transfer functions have to be differentiated further since multiple types exist (e.g., 1D intensity, 2D intensity-gradient, 2D LH [22], 3D [14]) and different segments may also have different transfer functions assigned to them. Incorporating all these parameters within the navigation algorithm would not be a trivial task, and if possible at all it would likely lead to code duplications, which would need to be updated to incorporate additional data sets or formats, new transfer function types, additional rendering parameters, etc.…”
Section: Design Considerationsmentioning
confidence: 99%
“…The Kindlmann's survey [7] explains many kinds of transfer functions, but only a few multidimensional transfer functions have been developed. As transfer function domains are extended to two and three dimensions, the function yields more power in feature selection [9] [10]. For the same reason, it is difficult to set values manually.…”
Section: Related Workmentioning
confidence: 99%
“…For the same reason, it is difficult to set values manually. Nevertheless Kniss et al [10] suggested a convenient user interface widgets for setting three-dimensional (3D) transfer functions. Users, however, still needed to decide voxel transparencies from the displayed information of the two-dimensional (2D) histogram of v and g, while selecting interesting regions.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations